The Relationship of Individual Characteristics and Farm Biosecurity Implementation with The Incident of Contact Dermatitis - Prahutami, Nadya Salma (Poltekkes Kemenkes Tanjung Karang, 2024)
Poultry workers risk contracting diseases due to physical or biological exposure. One such disease is contact dermatitis. This study aims to analyze the individual and the application of livestock biosecurity that can be associated with cases of contact dermatitis in cage workers. This study a descriptive-quantitative that uses a cross-sectional approach. The research was conducted at PT. X in June 2022. The sample of this study was 43 people who were taken through simple random sampling. Data was collected using questionnaires, interviews, and observations. The results were then tested using Chi-Square and Odds Ratio (OR) with a Confidence Level of 95%. The study showed that two variables were associated with contact dermatitis, namely cage ventilation (OR= 5.45; 95% CI: 1.21 - 24.43; P=0,020) and frequency of hand washing (OR= 2.70; 95% CI: 2.57 - 282.99; P=0,001). Meanwhile, variables that were not significantly related were age (P=0.306), gender (P=0.206), length of work (p=0.698), floor (P=1.000), and PPE usage (P=0.245). Poor environmental quality and personal hygiene practices could affect contact dermatitis in workers. Therefore, efforts are needed, such as occupational safety and health education for workers, routine health checks, and environmental inspections at PT. X.